Hemodynamics in Distally Based Sural Flaps for Lower Leg Reconstruction: A Literature Review - Türker, Tolga; Hines, Eric; Haddad, David (Journal of Hand and Microsurgery, 2022)
Coverage of posttraumatic and chronic wounds at the distal leg is a difficult problem due to limited soft tissue available for local flaps. The sural flap is a versatile and effective method for reconstruction in this area since it does not need a significant amount of time or assistance to complete. Improving the survival of these flaps is critically dependent on understanding the basics of flap circulation and why recent modifications were introduced. This review will serve as a much-needed comprehensive analysis of these topics for surgeons looking to increase the reliability of their sural flaps.
Keywords: sural flaps; tunneling; delayed; flap; pedicle